Nemesia Root Hair Response to Paper Pulp Substrate for Micropropagation. (4th January 2012) - Labrousse, Pascal; Delmail, David; Decou, Raphaël; Carlué, Michel; Lhernould, Sabine; Krausz, Pierre
Abstract : Agar substrates for in vitro culture are well adapted to plant micropropagation, but not to plant rooting and acclimatization. Conversely, paper-pulp-based substrates appear as potentially well adapted for in vitro culture and functional root production. To reinforce this hypothesis, this study compares in vitro development of nemesia on several substrates. Strong differences between nemesia roots growing in agar or in paper-pulp substrates were evidenced through scanning electron microscopy. Roots developed in agar have shorter hairs, larger rhizodermal cells, and less organized root caps than those growing on paper pulp. In conclusion, it should be noted that in this study, in vitro microporous substrates such as paper pulp lead to the production of similar root hairs to those found in greenhouse peat substrates. Consequently, if agar could be used for micropropagation, rooting, and plant acclimatization, enhancement could be achieved if rooting stage was performed on micro-porous substrates such as paper pulp.